Satisfaction Derived by the Users of Clinic Plus Shampoo in Coimbatore - Vijaykumar, R.; Prabha, P. V.; Raman, N. (Indian Journal of Marketing, 2007)
Long as well as healthy hair has been the dream of many people. People have been using various products in order to have healthy and lengthy hair. Shampoos are one among such products used by all classes of people since a long time back for the purpose of maintaining a healthy and lengthy hair. Many companies have been producing different varieties and flavours of shampoos to suit the varied requirements of the different classes of consumers. Hindustan Lever Limited (HLL), a pioneer in the field, has been offering a variety of shampoos for the consumers. Clinic plus is one of the leading and fast moving brands marketed by HLL. Hindustan Lever Limited (HLL) is India's largest Fast Moving Consumer Goods company, touching the lives of two out of three Indians with over 20 distinct categories in Home and personal Care Products and Foods and Beverages. They endow the company with a scale of combined volumes of about 4 million tones and sales of Rs.10, 000 crores. HLL is also one of the country's largest exporters. The company has been recognised as a Golden Super Star Trading House by the Government of India. HLL meets everyday needs for nutrition, hygiene, and personal care with brands that help people feel good, look good and get more out of life. Hall's brands - like Lifebuoy, Lux, Surf Excel, Rin, Wheel, Fair & Lovely, Pond's, Sunsilk, Clinic Plus, Pepsodent, Close-up, Lakme, Brooke Bond, Kissan, Knorr-Annapurna, Kwality Wall's - are household names across the country and span many categories - soaps, detergents, personal products, tea, coffee, branded staples, ice cream and culinary products. They are manufactured in close to 80 factories. The operations involve over 2,000 suppliers and associates. HLL's distribution network, comprising about 7,000 redistribution stockists, directly covers the entire urban population, and about 250 million rural consumers. Hence the present study has been conducted by the researchers with the primary objective of measuring the extent of variation in the level of satisfaction derived by the users of Clinic Plus Shampoo in Coimbatore and the factors which influence the satisfaction derived by the respondents. The study also offers constructive suggestions for improving the satisfaction derived by the users of the shampoo.